Sulfur and Selenium Modifications at Phosphorus Atom in Nucleoside Monophosphates, Activity and Potential Applications - Krakowiak, Agnieszka (Current Medicinal Chemistry, 2025)
Nucleotides and nucleosides play an essential role in many cellular processes but have low physiological stability, which limits their usefulness. Nucleosides modified with chalcogen at the phosphorus atom are more stable in body fluids and tissues. They can act as activators or inhibitors in many processes, including signal transduction through receptors and intracellular signaling. Some of them are also used as drugs or prodrugs that can serve as potential therapeutics in cancer and other diseases. This review focuses primarily on the activity and potential application of the nucleoside monophosphates modified with sulfur and selenium at the phosphorus atom, such as nucleoside 5’-O-phosphorothioate and 5’-O-phosphoroselenoates as well as adenosine cyclic 5’, 3’- monothiophosphate and guanosine cyclic 5’, 3’-monothiophosphate.
Keywords: hydrogen selenide (H2Se)